Reducing Defects Density and Enhancing Hole Extraction for Efficient Perovskite Solar Cells Enabled by π‐Pb2+ Interactions. (30th June 2021) - Wen, Lirong; Rao, Yi; Zhu, Mingzhe; Li, Ruitao; Zhan, Jingbo; Zhang, Linbao; Wang, Li; Li, Ming; Pang, Shuping; Zhou, Zhongmin
Abstract: Molecular doping is an of significance approach to reduce defects density of perovskite and to improve interfacial charge extraction in perovskite solar cells. Here, we show a new strategy for chemical doping of perovskite via an organic small molecule, which features a fused tricyclic core, showing strong intermolecular π‐Pb 2+ interactions with under‐coordinated Pb 2+ in perovskite. This π‐Pb 2+ interactions could reduce defects density of the perovskite and suppress the nonradiative recombination, which was also confirmed by the density functional theory calculations. In addition, this doping via π‐Pb 2+ interactions could deepen the surface potential and downshift the work function of the doped perovskite film, facilitating the hole extraction to hole transport layer. As a result, the doped device showed high efficiency of 21.41 % with ignorable hysteresis. This strategy of fused tricyclic core‐based doping provides a new perspective for the design of new organic materials to improve the device performance. Abstract : Featuring a fused tricyclic core, an organic small molecule was intentionally synthesized to reduce defects density and improve hole transportation in perovskite devices via π‐Pb 2+ interactions, confirmed by multiple characterizations and simulation.